Comparison of Optimal Pipe Sizing Designs for Pressurized Flow System - Arumugam, Aanandsundar; Habtay, Gedion; Kibrom, Haben; Gebreamlak, Medhanie (International Journal of Computer Sciences and Engineering, 2025)
Pipelines are normally designed to deliver fluid at the required head and flow rate in a cost effective manner. The selection of an optimum pipe size for pumping plants and pipelines in pressurized flow pipe network should be based on careful economic analysis. Increase in conduit diameter leads to increase in annual capital costs, and decrease in operating costs. The study presents an optimized pipe diameter selection for the farm located at Hamelmalo Agricultural College (HAC). Relationships were formulated connecting theories and principles of hydraulic and economic analysis of the pipe selection process. These were developed into a computer program, written in Java language, for a high- level precision estimate of the optimum pipe diameter. The optimum pipe diameter design primarily includes three major methods available in literature namely Pipe sizing design using Jack’s Cube method, design based on Head Loss Gradient method and design based on Smit’s method